Evaluating the accuracy and effectiveness of criminal geographic profiling methods: the case of Dandora, Kenya - Mburu, Lucy; Helbich, Marco (The professional geographer, 2015)
Criminal geographic profiling (CGP) prioritizes offender search, extensively reducing the resources expended in criminal investigations. The utility of CGP has, however, remained unclear when variations in environmental characteristics and offense type are introduced. This study evaluates several CGP strategies with data from Dandora, a small but densely populated suburb of Nairobi, Kenya. The research employs error distance and search-cost measures to determine CGP accuracy. Characterized by much shorter journeys to crime than those observed in Western cities, this study discovers significant applicability of CGP strategies in prioritizing offender searches. The negative exponential CGP strategy is identified to generate the most accurate geo-profiles.
Published online: 19 March 2014
Gesehen am 10.06.2020